The Measurement of Efficiency of Sharia Banks in Indonesia: Two-Stage Data Envelopment Analysis (DEA) - Aziz, Lukmanul Hakim; Ganika, Gerry; Mala, Chajar Matari Fath (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2023)
This research was conducted to measure the efficiency of sharia banks in Indonesia. The study utilized two stages, with the first stage employing the Data Envelopment Analysis (DEA) method, and the second stage conducting an analysis using the Tobit Method to determine the influence of market competition, market share, NSFR, CAR, ROA, and BOPO variables on its independent variable, which is efficiency. This research utilized panel data from sharia banks in Indonesia. The findings of this study provide a deeper understanding of the factors influencing the efficiency of sharia banks, and the results can serve as a basis for formulating policies that support the growth of a more efficient sharia banking industry. Several variables that affect sharia banks in Indonesia are market share, NSFR, CAR, ROA, and BOPO. However, variables such as the Lerner Index and ROA do not have a significant impact on the level of efficiency.